Effective Participation in the International Monitoring of the UNCRPD? The Experience of the Disability Movement from Three Case Studies in Europe - Hanxu Liu (Scandinavian Journal of Disability Research)
This article seeks to clarify the normative framework for the participation of organisations of persons with disabilities (OPDs) derived from Articles 4(3) and 33 of the UNCRPD, and to explore how OPDs have participated in the UNCRPD State reporting process in three case studies: Denmark, Hungary and France. The research draws on legal and qualitative research methods based on document analysis and interviews from the perspectives of OPDs, UN experts, and other stakeholders. It aims to contribute to the limited empirical research on the participation of European OPDs in the international monitoring of the UNCRPD. After discussing the experience and impact of these OPDs on the UN level, the article identifies the contributing factors and main challenges that have affected their effective participation in the context of EU countries.